CLINICAL-DIAGNOSTIC VALUE OF THE STUDY OF NEOPTERIN IN MYOCARDIAL INFARCTION ON THE BACKGROUND OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - A. V. Naumov; T. V. Prokofieva; L. V. Saroyantc; O. S. Рolunina (Кубанский научный медицинский вестник)
Aim. To determine the significance of the study of neopterin as a marker of the endo-genetic toxicity syndrome in patients with myocardial infarction on the background of chronic obstructive pulmonary disease.Materials and methods. 64 patients with cardiovascular and respiratory pathology and 29 somatically healthy individuals of the Astrakhan region as the con-controlling group were examined. Patients were divided into 3 groups: the first 20 patients with myocardial infarction, the second group – 21 patients with chronic obstructive pulmonary disease and the third 23 patients with a combination of these diseases.Results. In patients with chronic obstructive pulmonary disease in combination with infarction of myocardium revealed the highest values of neopterin in blood serum in comparison with patients with monoiodotyrosine and somatically healthy individuals. Comparison of the values of neopterin with a number of recognized clinical and laboratory markers of endogenous intoxication revealed a positive correlation with heart rate, lactic acid, leukocyte index of intoxication and the ratio of neutrophils/leukocytes.Conclusion. In the course of the study, the clinical diagnostic value of the study of neopterin as a marker of endogenous intoxication in patients in Parkton myocardial on the background of chronic obstructive pulmonary disease has been proved.